2017
DOI: 10.18869/nirp.bcn.8.3.213
|View full text |Cite
|
Sign up to set email alerts
|

Research Paper: The Modulatory Role of Orexin 1 Receptor in CA1 on Orofacial Pain-induced Learning and Memory Deficits in Rats

Abstract: Introduction:Cognitive impairment is commonly associated with pain. The modulatory role of orexin 1 receptor (OX1R) in pain pathways as well as learning and memory processes is reported in several studies. The current study was designed to investigate the possible role of CA1-hippocampal OX1R on spatial learning and memory of rats following capsaicin-induced orofacial pain.Methods:Orofacial pain was induced by subcutaneous intra lip injection of capsaicin (100 μg). CA1 administration of orexin A and its select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…It has been previously reported that pain can induce apoptosis in the brain cells (Kooshki et al., 2017 ). We found that MeJA treatment leads to a considerable increase in the BDNF gene levels while decreasing TNF‐α , IL‐1β , and COX‐2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that pain can induce apoptosis in the brain cells (Kooshki et al., 2017 ). We found that MeJA treatment leads to a considerable increase in the BDNF gene levels while decreasing TNF‐α , IL‐1β , and COX‐2 levels.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, the rats were divided into seven experimental groups at random (total number = 49, n = 7 per group). The sample size was calculated based on information from previous studies (Kooshki et al, 2016(Kooshki et al, , 2017Rahbar et al, 2019;Raoof et al, 2019Raoof et al, , 2022Shahsavari et al, 2018).…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Whereas, capsaicin-induced cognitive impairments have been shown to be reversed by analgesic drugs. [ 6 12 ]…”
Section: Introductionmentioning
confidence: 99%